Employee Empowerment and Job Satisfaction: A Literature Review - Ananda Sulistio; Ismi Darmastuti (LifeSciFi, 2022)
This literature review employs a scoping review methodology to synthesize research on the relationship between employee empowerment and job satisfaction across organizational contexts. The research begins by defining the primary question: how does employee empowerment impact job satisfaction in various industries? A review protocol is developed, setting specific inclusion criteria for studies published between 2019 and 2024, with additional supporting studies from 2014 to 2018. Exclusion criteria include studies not in English or Indonesian, or those not directly related to the topic. Relevant studies are gathered from databases such as ProQuest, Emerald, Scopus, and ResearchGate, using keywords like